Protocole de kyoto : Le cas du secteur résidentiel au Canada? - Gaétan Lafrance; Julien Genois; Martin Lemay (VertigO)
This paper compares unit space heating energy consumptions (USHEC) per household in the Canadian residential sector. The study is based on several surveys conducted by Hydro-Québec and Natural Resource Canada. The approach used to estimate USHEC is the conditional demand analysis (CDA). A comparison between Québec and other Canadian regions seems to show that Québec consumes less energy per household for space heating than other regions in Canada. A further analysis seems to show that the Québec dwelling stock appears more efficient in many aspects. Taking lessons from these comparisons, simple options as lowering heating temperature and a better control of burner can be applied in the Canadian residential sector to reach the Kyoto Protocol.